LabVIEW Instruments for Creating Brain-Computer Interface Applications by Simulating Graphical Animations and Sending Text Messages to Virtual and Physical LEDs Based Display Systems Connected to Arduino Board - Ruşanu, O A (IOP Publishing, 2022)
The brain-computer interface (BCI) is a multidisciplinary research field aimed at helping people with neuromotor disabilities. A BCI system enables the control of mechatronic devices by using cognitive intentions translated into electroencephalographic signals. This paper presents the implementation of LabVIEW-based display systems that can be controlled by a brain-computer interface based on detecting the voluntary eye blinks used as commands. The interactive virtual or physical display systems are helpful thanks to running or simulating various graphical animations or transmitting different text messages in a user-customizable way. The proposed LabVIEW-based virtual display systems provide versatile functionalities such as: customizing the own visual animations and the movement of any text message by switching the direction (to the left or to the right) depending on the user’s choice. This paper presents five original virtual LEDs based display systems developed in LabVIEW graphical programming environment. The implemented LabVIEW applications included: an 8x8 LEDs matrix for simulating graphical animations, 2x16 LCD TEXT for showing text messages, and a 7-segments display for implementing chronometer functionality. Moreover, the LabVIEW virtual display systems were interfaced with the physical display systems (8x8 LEDs matrix controlled by MAX7219 driver and 2x16 LCD TEXT) connected to the Arduino Uno board.